Rancang Bangun Sistem Informasi Situs Bersejarah Berbasis Web - Aditia, Dwi Rino; Widyanto, R.Arry; Primadewi, Ardhin (Universitas Muhammadiyah Magelang, 2019)
Historic sites are a form of heritage and cultural heritage of ancestors that have value for the life of the nation today and in the future. Magelang City is one city that has many historic sites that have not been optimally managed. The k-medoid algorithm is a method used in creating groups based on objects as representatives (medoid) which function as cluster centers for each cluster. In this research, web-based historic site information system design in Magelang City is carried out. Through the information system that has been built to provide a friendly user information retrieval that has many advantages such as searching, grouping and information data accessed by visitors.